Coordenação pedagogica e formação continuada: um diálogo sobre a proposição de formação continua na SEMED de Alto Alegre do Pindaré - SILVA, Valda Ribeiro da Cruz (2023)
This research aimed to analyze the challenges faced by the Coordinators of the Educational Core of SEMED (Municipal Department of Education), in Alto Alegre do Pindaré, regarding the implementation of continuous training for school coordinators within the educational network, aiming to develop theoretical and methodological recommendations that would contribute to the proposition of formative processes for teachers. To achieve this, a collaborative research approach was employed, based on the elements of action research formation. Thus, we selected fourteen pedagogical coordinators from SEMED in Alto Alegre do Pindaré as collaborative participants in the research, who work in various areas of education and segments of Basic Education, Early Childhood Education, Regular and Multigrade Elementary Education, and Youth and Adult Education. The data generation procedures included narrative interviews, pedagogical meetings, and reflective sessions. The interpretation and systematization of the data utilized the writing technique called reflexive narrative. Throughout this investigative journey, we relied on the theoretical contributions of Imbernón (2011), Tardif (2018), Placco (2015), Domingues (2014), André (2016), Freire (2018), Fusari (2011), Ibiapina (2008), Almeida (2015), Garrido (2015), among others, who present conceptions and strategies on continuous training for education professionals, along with other authors who were necessary during the research process. With the support of the research collaborators, it was possible to confirm that pedagogical coordinators, as trainers of trainers within the public education network of the municipality, require greater investment from public authorities in their professional practice, specifically in continuous training to support their personal and professional development. However, it is understood that if the primary action of the pedagogical coordinator is to propose continuous training for educators and ensure the quality of the teaching and learning process, the need for investment in their continuous training is undeniable, both for SEMED and school pedagogical coordinators. Based on the research findings, a collaborative effort was made to systematize a handbook/resource with theoretical and methodological recommendations aimed at proposing formative processes for coordinators/trainers and teachers within the municipal education network.